Strategies for achieving the international development targets : environmental sustainability and eliminating poverty : consultation document (DFID LondonGB, 2000)
Looks at the ways that the international community might attempt to meet the international development target for the environment and sustainable development. Argues that development will not be sustainable without effective management of the environment, and that equal attention needs to be given to the three social, economic and environment pillars of sustainable development.
Keywords: SUSTAINABLE DEVELOPMENT